Prvih osemdeset let spektroskopije Augerjevih elektronov - Južnič, Stanislav (Vakuumist, 2003)
We researched the early results of bombarding matter with electrons. We described the events around the discovery of Auger spectroscopy, also connected with the first successful woman scientific researcher, Lise Meitner. We explained why so much time elapsed before the industrial use of Auger spectroscopy. We listed the strong sides of Auger method in modern industry. The special concern was put on application of Auger method in Slovenia.
Keywords: Augerjeva spektroskopija; spektroskopija; tanke plasti; zgodovinski pregledi